Fatigue reliability assessment of coupled spar-mooring system - Jameel, M.; Ahmad, S.; Asme, M (Amer Soc Mechanical Engineers, 2011)
Spar platform is a compliant floating structure used for exploration of oil and gas from deep sea. To ensure safe operations, reliability against mooring line failure is a major concern in design. Furthermore, the mooring lines have high investment costs and are normally not accessible for in-service inspection. The common approach for solving the dynamics of Spar system is to employ a decoupled quasi-static approach which ignores the platform and mooring lines interaction. Coupled analysis, used presently, considers the mooring lines and platform in an integrated single model. Hence, it effectively captures the damping effect due to Spar and mooring lines coupling. Finite element code ABAQUS is used to obtain the response of Spar-mooring system under long crested random sea with current. Limit state function is derived based on failure due to fatigue for probabilistic reliability assessment. Random variables, participating actively in the limit state function are identified and statistically modeled. The most probable points or the design points are found to be an effective parameter for estimating partial factors of safety for load and resistance variables. First Order Reliability Method (FORM) is used to calculate probability of failure and reliability indices. The results are later checked against Monte carlo simulation. Reliabilities of segmental length of mooring and of full length are determined as they may significantly differ if the mooring properties change along the length. Reliability indices of annual and life time sea states are calculated.